Stratospheric aerosol injection tactics and costs in the first 15 years of deployment - Wake Smith; Gernot Wagner (Environmental Research Letters, 2018)
We review the capabilities and costs of various lofting methods intended to deliver sulfates into the lower stratosphere. We lay out a future solar geoengineering deployment scenario of halving the increase in anthropogenic radiative forcing beginning 15 years hence, by deploying material to altitudes as high as ∼20 km. After surveying an exhaustive list of potential deployment techniques, we settle upon an aircraft-based delivery system. Unlike the one prior comprehensive study on the topic (McClellan et al 2012 Environ. Res. Lett. 7 034019), we conclude that no existing aircraft design—even with extensive modifications—can reasonably fulfill this mission. However, we also conclude that developing a new, purpose-built high-altitude tanker with substantial payload capabilities would neither be technologically difficult nor prohibitively expensive. We calculate early-year costs of ∼$1500 ton ^−1 of material deployed, resulting in average costs of ∼$2.25 billion yr ^−1 over the first 15 years of deployment. We further calculate the number of flights at ∼4000 in year one, linearly increasing by ∼4000 yr ^−1 . We conclude by arguing that, while cheap, such an aircraft-based program would unlikely be a secret, given the need for thousands of flights annually by airliner-sized aircraft operating from an international array of bases.